1990
DOI: 10.1212/wnl.40.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of the immune reaction in the nervous system in paraneoplastic encephalomyelitis

Abstract: We examined frozen sections of frontal cortex, medulla, and dorsal root ganglia from a patient with small-cell lung cancer and paraneoplastic encephalomyelitis, involving the medulla and dorsal root ganglia, with a panel of antibodies reactive for IgG, IgM, C3, B cells, T cells, T cell subsets, macrophages, and class I and II (HLA-DR) major histocompatibility complex (MHC) antigens. We detected an antineuronal antibody (anti-Hu) in the serum and CSF of the patient and found deposits of IgG in the periphery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 0 publications
3
45
0
2
Order By: Relevance
“…þ T-cell infiltrates in the central nervous system (CNS), although the direct target antigen of these T cells is unknown (Graus et al 1990;Posner 1991;Jean et al 1994;Verschuuren et al 1996;Giometto et al 1997;Dalmau et al 1999;Bien et al 2012). These T cells, reminiscent of those reported in RE, are found in the vicinity of neurons where they are posed to release cytotoxic granules and may, therefore, be directly involved in neuronal cell death (Tanaka et al 1998(Tanaka et al , 1999Bernal et al 2002;Bien et al 2002Bien et al , 2012Blumenthal et al 2006).…”
Section: Immunity and Inflammation In Epilepsymentioning
confidence: 99%
“…þ T-cell infiltrates in the central nervous system (CNS), although the direct target antigen of these T cells is unknown (Graus et al 1990;Posner 1991;Jean et al 1994;Verschuuren et al 1996;Giometto et al 1997;Dalmau et al 1999;Bien et al 2012). These T cells, reminiscent of those reported in RE, are found in the vicinity of neurons where they are posed to release cytotoxic granules and may, therefore, be directly involved in neuronal cell death (Tanaka et al 1998(Tanaka et al , 1999Bernal et al 2002;Bien et al 2002Bien et al , 2012Blumenthal et al 2006).…”
Section: Immunity and Inflammation In Epilepsymentioning
confidence: 99%
“…In particular, passive transfer of IgG from anti-Hu patients to animals did not cause the disorder, and animal immunization with Hu-D protein or cDNA resulted in synthesis of high titers of antibodies but without modeling the disease [7,8]. There is increasing evidence that cellular immunity is involved in the pathogenesis of the disease [9][10][11][12]. We have previously shown that the Hu-D fusion protein is a specific target of patients' auto-reactive circulating CD4+ T cells, presumably of Th1 subtype [13].…”
Section: Introductionmentioning
confidence: 99%
“…28,132 Dorsal root ganglia from such patients demonstrate destruction of neurons and perivascular and perineuronal inflammatory infiltrates, in particular CD8 + (cytotoxic) T cells, but also B cells, microglia, and macrophages. 28,50 These pathologic changes are similar to those seen with the sensory ganglionitis of Sjogren's disease. 52 Almost all patients with paraneoplastic sensory neuronopathy have polyclonal IgG antibodies in both serum and cerebrospinal fluid to a class of neuronal proteins called Hu antigen.…”
Section: Paraneoplastic Neuropathiesmentioning
confidence: 56%
“…104,132 Additionally, Huspecific B and T lymphocytes have also been found in the inflammatory infiltrates. 50 Interestingly, homology has also been demonstrated between HuD and a major antigen recognized by the sera from some patients with Sjogren's disease, R0-52kD. 103 RO-52kD has been shown to be expressed in a small-cell lung carcinoma cDNA library.…”
Section: Paraneoplastic Neuropathiesmentioning
confidence: 99%